2011
DOI: 10.1007/s10689-011-9425-2
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2 genetic testing uptake and psychosocial outcomes in men

Abstract: Few studies have quantitatively evaluated the uptake and outcomes of BRCA1/2 genetic counseling and testing in men. We conducted a prospective longitudinal study to describe and compare uptake of and psychosocial outcomes following BRCA1/2 testing in a sample of men and women at high-risk for carrying a BRCA1/2 mutation. Men (n = 98) and women (n = 243) unaffected with cancer completed baseline assessments prior to genetic counseling and testing and then 6- and 12-months post-testing. Most men (n = 94; 95.9%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…53 Other studies have not reported any change in psychological risk with positive test results. 32,33,40,[57][58][59][60][61][62] Nonetheless, women who test positive for BRCA1/BRCA2 are also often met with resistance, shock, and other negative emotions from family members. [63][64][65][66] Similarly studies of individuals undergoing HNPCC testing demonstrate that the individual experiences of both unaffected and affected carriers are varied, but the majority experience an overall decrease in anxiety and depression.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…53 Other studies have not reported any change in psychological risk with positive test results. 32,33,40,[57][58][59][60][61][62] Nonetheless, women who test positive for BRCA1/BRCA2 are also often met with resistance, shock, and other negative emotions from family members. [63][64][65][66] Similarly studies of individuals undergoing HNPCC testing demonstrate that the individual experiences of both unaffected and affected carriers are varied, but the majority experience an overall decrease in anxiety and depression.…”
Section: Impact Of Genetic Test Resultsmentioning
confidence: 99%
“…In fact, Graves et al recently reported that uptake was not different between males and females in their study, in which genetic counseling and testing were provided free of charge. 17 In contrast, Finlay et al reported higher completion rates of genetic testing in female compared to male first-degree relatives (73% vs. 49%) and second-degree relatives (68% vs. 43%) of BRCA mutation carriers (p<0.01). 18 Finally, Evans et al concluded that male family members had a substantially higher uptake of genetic testing, suggesting utility of proactive approaches to ensure these high risk men receive appropriate information.…”
Section: Discussionmentioning
confidence: 92%
“…In a meta-analysis of mood disorder prevalence in cancer settings, there was less interviewer-defined depression and anxiety than anticipated in cancer patients, although a combination of various mood disorders occurred in 30-40% of hospitalized cancer patients [35]. In a study of long-term distress in a sub-set of men with BRCA1/2 mutations, predictors of distress included higher baseline distress and being unmarried [15], whereas, most of our distressed participants were married and all but one were affected with TC. The sources of the reported distress have yet to be resolved [6,36-38].…”
Section: Discussionmentioning
confidence: 99%
“…Feelings of heightened intimacy and bonding, satisfying sexual relations, and intimate involvement in the illness experience can contribute to overall adjustment [6,54]. Single men, a vulnerable group, will also undoubtedly also benefit from the opportunity to process their experiences over time [15]. Friendship relationships both in terms of long-term buddies from childhood and adolescence and those developed through members of a sports team, a comparatively neglected area of inquiry, could be further investigated as sources of social support, opinion molding and decision-making in familial cancer families as well as other male-associated cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation